Renewed interests in carbonic anhydrase IX in relevance to breast cancer treatment - Mitra Dolatkhah (BioImpacts, 2019)
The highly proliferating cancerous cells can form permissive accommodating milieu – the so-called tumor microenvironment (TME). During the initiation of solid tumors, hypoxia plays a key role in glycolysis, which can trigger the anomalous overexpression of several enzymes and transporters involved in the metabolism of glucose. Of these, carbonic anhydrases (CAs), especially CAIX, together with other molecular machinery involved in the production/trafficking of acidic byproducts, play key roles in the regulation of intracellular and extracellular pH. CAIX, along with other molecular machinery of cancer cells such as Na+/H+ exchanger 1 (NHE1) and V-type H+-ATPase (V-ATPase), alkalinizes the tumor cells and maintains the acidic pH condition within the extracellular fluid of the TME. It facilitates the progression and metastasis of cancer and intensifies the migration and invasion of cancer cells. Thus, inhibition of CAIX can be considered a highly effective and promising therapeutic strategy in the treatment of aggressive tumors.